Factores que influyen en la lealtad del cliente del chifa Fast Food Iquitos 2022 - Murrieta Garcia, Anthony Kevin (2023)
The purpose of this thesis project was to identify the factors that have the greatest influence on customer loyalty of Chifa - Fast Food, Iquitos 2022, opting for a basic study, descriptive and explanatory level, non-experimental design. The population consisted of 331 people, from which a sample of 178 clients was extracted, to whom a survey and a questionnaire of 25 items were applied. It was concluded that the variables that would be significantly predicting customer loyalty are food quality (sig.=0.000), atmosphere (sig.=0.005) and satisfaction (sig.=0.050), however, the variables price (sig.=0.703), quality of service (sig.=0.387) and location (sig.=0.336) do not significantly predict the level of loyalty. Therefore, the quality of the food (39.2%), the price (3.3%), quality of service (36.3%), the atmosphere (37.7%), location (14.1%) and satisfaction (38.5%) maintains a significant influence with the customer loyalty of Chifa - Fast Food, Iquitos 2022